1874-1875: The Birth of a Fashion Heritage Consciousness in France - Maude Bass-Krueger (In Situ)
The first exhibition about the history of costume, the “Musée historique du costume” was inaugurated in France in 1874. One year later, the historian and archaeologist Jules Quicherat (1814-1882) published the first popular book about French dress history, l'Histoire du costume en France depuis les temps reculés jusqu'à nos jours (Hachette, 1875). The exhibition and the book were immensely popular. This article seeks to understand the nascent interest in the material culture of fashion that they both revealed. A closer examination of how the organizers chose to display the objects in the “Musée historique du costume”, as well as the way they instructed the visitor to see what was in the exhibition, reveals the very first institutional framework for public interaction with historical fashion objects. The analysis of the Histoire du costume, and in particular a careful examination of the method used by Quicherat, shows how Quicherat succeeded in integrating fashion objects as sources into a larger historic narrative.